2015
DOI: 10.1088/1748-9326/10/3/034015
|View full text |Cite
|
Sign up to set email alerts
|

Significant influence of fungi on coarse carbonaceous and potassium aerosols in a tropical rainforest

Abstract: Fungal spores are ubiquitous in the Earth's atmosphere, especially in the environment of tropical rainforests with intense biological activities. To assess the impact of fungi on chemical components of atmospheric aerosols at a Chinese tropical rainforest site, size-segregated fungal spore tracers (i.e. arabitol and mannitol) were measured along with major aerosol components, including carbonaceous species and water-soluble inorganic ions. The fungal spore tracers were found to be predominately associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 29 publications
9
36
2
4
Order By: Relevance
“…Potassium, Cu, and Zn are considered to be tracer elements of biogenic emissions from the rainforest. Potassium in submicron aerosols also has a source from vegetation fires and is frequently used as a tracer for biomass burning aerosols (Andreae et al, 1983;Martin et al, 2010;Zhang et al, 2015). Soil-dust-related elements are typically present at the highest concentrations during the early wet-to-dry season transition (May), as has been shown in previous studies (Pauliquevis et al, 2012;Andreae et al, 2015).…”
Section: Composition Of Aerosol Soluble Fractionmentioning
confidence: 62%
“…Potassium, Cu, and Zn are considered to be tracer elements of biogenic emissions from the rainforest. Potassium in submicron aerosols also has a source from vegetation fires and is frequently used as a tracer for biomass burning aerosols (Andreae et al, 1983;Martin et al, 2010;Zhang et al, 2015). Soil-dust-related elements are typically present at the highest concentrations during the early wet-to-dry season transition (May), as has been shown in previous studies (Pauliquevis et al, 2012;Andreae et al, 2015).…”
Section: Composition Of Aerosol Soluble Fractionmentioning
confidence: 62%
“…OC, accounting for 7-80 % of PM mass, constitutes a significant fraction of atmospheric aerosols (Yu et al, 2004;Ram et al, 2012;Ho et al, 2012). Ambient fungi are considered a possible source of OC in PMs.…”
Section: Contribution Of Spores To Oc Concentrations and Pm Massmentioning
confidence: 99%
“…Glomerella was widely found on the surface of leaves, suggesting that leaf senescence is an important source of fungi in PM 2.5 in autumn . Some crucial environmental factors having a potential influence on fungal release and growth, such as temperature; NO 2 ; PM 10 ; SO 2 ; CO; relative humidity (Yan et al, 2016); radiation; vegetation (Moreau et al, 2016); urbanization; and accidental events, e.g., dust storms (Prospero et al, 2005), rainfall (Zhang et al, 2015), hurricanes (DeLeon-Rodriguez et al, 2013), and haze (Yan et al, 2016), have been identified. Herein Spearman's rank coefficient analysis indicated that Ca 2+ , a typical water-soluble inorganic ion from dust, was negatively related to the prevalence of Glomerella and Zasmidium in autumn (Fig.…”
Section: Size Distribution and Seasonal Variation Of Fungal Communitiesmentioning
confidence: 99%
“…In an intercomparison between the two different measurement techniques, Healy et al (2014) found that, while there was agreement in total number concentrations, the counts in the fluorescence channels of the WIBS (particularly FL1) were substantially higher than the UV-APS fluorescence counts, which would at least partly explain the difference here. The wetter, more humid conditions during the wet season measurement period of Huffman et al (2012) would be expected to favour emission (Jones and Harrison, 2004;Zhang et al, 2015). On the other hand, the higher rainfall would also result in enhanced wet deposition during the wet season, especially above canopy.…”
Section: Coarse-mode Aerosolmentioning
confidence: 99%
“…Strong vertical gradients in biological particles are therefore regularly seen in rainforest environments, and would be an additional factor in the differences observed between the measurements at TT34. In a remote tropical rainforest in China, Zhang et al (2015) estimated fungal spore concentrations to be around 50 L −1 based on chemical analysis of filters, and found higher concentrations associated with rainfall events. A global modelling study by Spracklen and Heald (2014) found simulated surface annual mean concentrations of fungal spores to be around 100 L −1 over tropical forests (including central Amazonia), which is consistent with this and other measurements at this site.…”
Section: Coarse-mode Aerosolmentioning
confidence: 99%